간호⋅간병통합서비스병동 간호사를 위한 낙상예방교육프로그램 효과 - 조은경(Eun-Gyeong Jo); 성미현(Mihyeon Seong); 이윤신(Yoonshin Lee); 석소현(Sohyune Sok) (한국콘텐츠학회 논문지, 19(11), 2019)
This study was to examine the effects of fall prevention educational program on the related knowledge, attitude, and self-efficacy of nurses working in Comprehensive Nursing Care Unit, general hospital. A quasi-experiment with a nonequivalent control group non-synchronized design was used, Participants included a total of 40 nurses as the subjects (Intervention: n=20, Control: n=20) working in Comprehensive Nursing Care Unit, general hospital, Seoul. Data were collected form March through May, 2017. Data were analyzed by using the SPSS/WIN 21.0 program. Intervention group showed significant higher knowledge (F=189.03, p<.001), attitude (F=761.74, p=.003), and self-efficacy (F=188.50, p=.002) scores than them of control group. The fall prevention educational program was an effective intervention for improving the related knowledge, attitude, and self-efficacy of nurses working in Comprehensive Nursing Care Units, general hospital. Therefore, the results show the necessity of developing and applying the systemic nursing intervention to improve preventive behavior on falls. 본 연구는 종합병원 간호 간병통합서비스 병동 간호사의 노인 낙상에 대한 지식과 태도, 낙상예방 자기효능감에 대한 낙상예방교육프로그램의 적용효과를 파악하고자 시도된 비동등성 대조군 전후 시차설계에 의한 유사실험연구이다. 연구대상자는 S시 소재 D종합병원 간호·간병통합서비스 병동에 근무하는 간호사로 실험군, 대조군 각 20명씩 40명을 대상으로 하였으며, 예비교육 프로그램은 타당도 검증을 거쳐 낙상예방교육프로그램을 개발하였다. 자료수집은 2017년 3월부터 5월까지였으며, 수집된 자료는 SPSS/WIN 21.0 프로그램을 사용하여 분석하였다. 연구결과 실험군은 대조군보다 지식(F=189.03, p<.001), 태도(F=761.74, p=.003), 낙상예방 자기효능감(F=188.50, p=.002) 점수가 유의하게 높았다. 결과적으로 낙상예방교육프로그램은 간호·간병통합서비스 병동에 근무하는 간호사의 노인 낙상에 대한 지식, 태도, 낙상예방 자기효능감을 향상한 효과적인 중재로 검증되었다. 따라서 간호·간병통합서비스병동 임상실무 현장에서 간호사의 낙상예방행위를 증가시키기 위한 체계적인 교육중재를 제공할 필요가 있다.